Effect of Preoperative Finasteride on the Volume orLength Density of Prostate Vessels,Intraoperative,Postoperative Blood Loss during and after Monopolar Transurethral Resection of Prostate:A Dose Escalation Randomized Clinical Trial Using Stereolog Method - Aminsharifi, Alireza; Salehi, Alireza; Noorafshan, Ali; Aminsharifi, Amirhossein; Alnajar, Khalil (Urology Journal, 2016)
Purpose: To evaluate the effects of two preoperative treatment courses with Finasteride on intraoperative and postoperative bleeding complications and prostate blood vessel characteristics in men who underwent transurethral resection of prostate (TURP) using monopolar energy. Materials and Methods: Men scheduled for TURP were randomized into group 1 (control n = 25, no medication), group 2 and 3 (n = 20 in each, 5 mg Finasteride daily for 2 and 4 weeks before TURP; respectively). Hematocrit level in the irrigation fluid, weight of the resected prostate chips, decreases in blood hemoglobin (Hb) level 6 and 24 hours after the operation together with volume and length density of prostate vessels using stereological methods were compared. Results: The three groups were matched regarding preoperative demographic data, resection time and weight of the resected tissue. Men who received preoperative Finasteride (groups 2 and 3) had significantly lower hematocrit levels in irrigation fluid than control group (control, 0.59 ± 0.85, group 2, 0.25 ± 0.4, group 3, 0.175 ± 0.16; P = .028; Power = .80). However, no statistically significant difference was found in hematocrit level in irrigation fluid between groups 2 and 3 (0.25 ± 0.4 vs. 0.175 ± 0.16, 95% confidence interval (CI) = -0.28-0.42; P = .68). These values were independent of the weight of the resected tissue and resection time. There were no significant differences between the three groups in the decrease in Hb 6 hours (P = .58) and 24 hours after TURP (P = .65). The stereological and histological characteristics of blood vessels in suburethral prostate tissue were similar in all three groups. Conclusion: A 2-week preoperative course of daily Finasteride seems sufficient to significantly reduce intraoperative blood loss; this effect was independent of the weight of the resected tissue and resection time. Neither the 2-week nor the 4-week presurgical Finasteride regimen could significantly decrease postoperative blood loss, and neither regimen induced significant changes in characteristics of prostate tissue blood vessels.